1988
DOI: 10.2466/pms.1988.66.3.997
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age, Sex, Hearing Loss and Balance on Development of Catching by Deaf Children

Abstract: 132 deaf boys and girls were evaluated on development for catching and static and dynamic balance proficiency. Additional information was obtained relative to age and hearing loss in decibels. Mature form in catching was related to chronological age and proficiency of balance. Sex and hearing loss do not appear to affect level of development as measured for catching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Balance was assessed using the modified stork stand and heel-toe balance beam subtests from the short form of the Bruininks-Oseretsky Test of Motor Proficiency (Butterfield, 1987). Age, dynamic balance, and static balance contributed to the discriminant functions for jumping (Butterfield & Ersing, 1987a), kicking (Butterfield & Ersing, 1987b), catching (Butterfield & Ersing, 1988), throwing (Butterfield, 1989), and running (Butterfield, 1991). Gender did not contribute to function for any of the five skills.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Balance was assessed using the modified stork stand and heel-toe balance beam subtests from the short form of the Bruininks-Oseretsky Test of Motor Proficiency (Butterfield, 1987). Age, dynamic balance, and static balance contributed to the discriminant functions for jumping (Butterfield & Ersing, 1987a), kicking (Butterfield & Ersing, 1987b), catching (Butterfield & Ersing, 1988), throwing (Butterfield, 1989), and running (Butterfield, 1991). Gender did not contribute to function for any of the five skills.…”
mentioning
confidence: 90%
“…The most definitive investigations of the fundamental motor skills of persons who are deaf were conducted by Butterfield (Butterfield, 1986(Butterfield, , 1987(Butterfield, , 1989(Butterfield, , 1991Butterfield & Ersing, 1987a, 1987b). Butterfield's sample for these studies included 75 boys and 57 girls aged 3-14 years from schools for students who are deaf.…”
mentioning
confidence: 99%
“…Various authors reported that audition is important in orienting eye, head, and body in the environment. Infants are capable of directing their eyes and head to auditory targets [1,3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Auditory stimulus plays important role in the direction of visual movements and orientation in the space [1][2][3][4]. Various authors reported that audition is important in orienting eye, head, and body in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to maintain and control balance is usually recognized as a fundamental motor component (Gregory Payne & Isaacs, 1991). In children with hearing impairment, the sensory organization balance function is significantly correlated with the gross motor abhty tested by the Bruininks-Oseretsky Test of Motor Proficiency (Butterfield & Ersing, 1988;Butterfield, 1991). In children with spastic cerebral palsy, only independent walkers, not nonwalkers, have stepping reactions (Gunsolus, Welsh, & Houser, 1975).…”
mentioning
confidence: 99%